Public Actors in Private Markets: Toward a Developmental Finance State - Robert C. Hockett; Saule T. Omarova (Washington University Law Review, 2015)
The recent financial crisis brought into sharp relief fundamental questions about the social function and purpose of the financial system, including its relation to the “real” economy. This Article argues that, to answer these questions, we must recapture a distinctively American view of the proper relations among state, financial market, and development. This programmatic vision—captured in what we call a “developmental finance state”—is based on three key propositions: (1) that economic and social development is not an “end-state” but a continuing national policy priority; (2) that the modalities of finance are the most potent means of fueling development; and (3) that the state, as the most potent financial actor, both must and often does pursue its developmental goals by acting endogenously—i.e., as a direct participant in private financial markets. In addition to articulating and elaborating the concept of the developmental finance state, this Article identifies and analyzes the principal modalities through which the modern American developmental finance state operates today. Finally, the Article proposes three broad strategic extensions of the existing modalities, with a view to enabling the emergence of a more ambitiously proactive and effective developmental finance state—and thus rediscovering a truly public-minded finance.
Keywords: Financial crisis; Developmental finance state; Public actor; Financial market